ENHANCING EFL INDONESIAN STUDENTSâ WRITING ABILITY AND MOTIVATION THROUGH FACEBOOK-INKSHEDDING - Rahmah, Nur Alfa (English Department of Faculty of Tarbiyah and Teachers Training, 2015)
This paper is attempted to propose a breakthrough alternative in the EFL teaching to enhance studentsâ ability and motivation in writing through facebook-inkshedding. The current development of technology and teenagerâs close relationship with online social networking demands English instructor to be more creative in choosing the medium that suit the studentsâ interest and teenage trend. Facebook nowadays possess a prominent position among other social network media that makes it a very potential learning media. Inkshedding, on the other side, is a very effective strategy to boast studentsâ creative ideas and confidence in writing. It brings an active discussion into written form and trigger students to express their mind in the target language and make them get used of it gradually. Not only that facebook-inkshedding exists beyond time and physical boundary, it can also grow studentsâ sense of community and motivate them to develop independently.